2019
DOI: 10.1080/23294515.2019.1592264
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Debate About Post-trial Access to Medical Interventions: A Qualitative Study of Participant Experiences at the End of a Trial Investigating a Medical Device to Support Type 1 Diabetes Self-Management

Abstract: Increasing ethical attention and debate is focusing on whether individuals who take part in clinical trials should be given access to post-trial care. However, the main focus of this debate has been upon drug trials undertaken in low-income settings. To broaden this debate, we report findings from interviews with individuals (n ¼ 24) who participated in a clinical trial of a closed-loop system, which is a medical device under development for people with type 1 diabetes that automatically adjusts blood glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 34 publications
5
34
0
Order By: Relevance
“…These findings suggest that regular, ongoing reviews of individuals using closed‐loop systems will be essential, in line with recommendations for those using other diabetes technologies . Even if clear guidance is put in place for when to remove a closed‐loop system, this may still be a very challenging task , and effective team working may be vital .…”
Section: Discussionmentioning
confidence: 81%
“…These findings suggest that regular, ongoing reviews of individuals using closed‐loop systems will be essential, in line with recommendations for those using other diabetes technologies . Even if clear guidance is put in place for when to remove a closed‐loop system, this may still be a very challenging task , and effective team working may be vital .…”
Section: Discussionmentioning
confidence: 81%
“…Many cited a need for on-going monitoring of trial participants for some time following trial exit. The same concern has been expressed by several other authors (Lawton et al (2019), and Bukenya, Seeley, Tumwekwase, Kabunga, and Ruzagira (2020)) who demonstrate that additional follow up and support of HIV positive clients following linkage to care significantly improved their general outcomes. The need to compensate trial participants for their engagement in research was another issue raised in the current study, .…”
Section: Discussionmentioning
confidence: 59%
“…The copyright holder for this this version posted November 16, 2020. ; https://doi.org/10.1101/2020.11.14.20231720 doi: medRxiv preprint 1 1 important to reduce negative emotional effects associated with trial closure (Lawton et al, 2019), and to offer guidance to participants on the next steps in accessing HIV care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants eagerly awaited their appointments with the dietitian, and the cessation of the intervention at 18 weeks shocked and saddened them, as they felt a keen sense of loss. These psychological and emotional effects on participants at the conclusion of trials have been reported in a number of other qualitative articles examining postintervention transition to usual care, with participants reporting a sense of loss, disappointment, anxiety, and isolation [32,33]. This highlights the need to incorporate how to manage the psychological impacts of abrupt cessation of intensive interventions on trial participants in the future [33].…”
Section: A Sense Of Support and Security Through Relationship Buildinmentioning
confidence: 76%